(untitled) (International Journal of Studies in Nursing, 2018)
In children developmental disorders expresses themselves by a variable presentation of symptoms and frequent manifestation of comorbidity of a complex nature. In addition to the classification of a disorder, individualising diagnostics is a means to realize assessment and treatment that are fine-tuned to the child. In the day to day care of children with a developmental disorder the Instrument for assessing the Child’s Constitution (ICC) is a supporting means to map out the child’s individual situation. The instrument is based on an anthroposophic anthropology and typology. It provides an individualised diagnosis by mapping the degree of (dis)balance in child development. In three developmental fields, the cognitive, the affective and the conative field, the (dis)balance of functioning is assessed by the ICC. The instrument consists of two parts. With reference to the three fields part I consists of 36 items, each having a subscale with 12 polar formulated items on a seven-point scale. For each of the three fields part II includes a visual analogue scale (VAS). The results of Part I and II are made comparable by putting them both on a ten-point scale. The results are graphically represented as a profile of the constitution. In this article we present the results of a study with the ICC on psychometric properties in a research group (n=535) and a control group (n=148). As reference of the assessment of the quality of the ICC a Consensus-based Standard for the selection of health Measurement Instruments is used.